Ugarit, Canaan, and Israel - Craigie, Peter C. 1938-1985 (1983)
A paper exploring the relationship between the Old Testament and one part of its ancient environment, namely Syria-Palestine, or the Eastern Mediterranean seaboard.
Keywords: Archaeology; Ancient Near East; canaan; Old Testament; Ugarit